Synthesis of CaCO3 and trimethyl borate by reaction of ulexite and methanol in the presence of CO2 - Özekmekçi, Mehtap; Çopur, Mehmet (Elsevier Sci Ltd, 2020)
Developing CO2 capture and use of technologies to reduce anthropogenic emissions can be part of the solution against climate change. The purpose of this study is to develop a novel method to synthesize CaCO3 and trimethyl borate solution by utilizing and capturing carbon dioxide in a high pressure reactor. Dissolution of ulexite has been investigated to determine the effect of important working parameters by using Taguchi method. The parameters and their ranges were given as follows: reaction temperature, 80-120 degrees C; pressure, 10-30 bar; solid-to liquid ratio, 5/100-20/100 g/mL; particle size,-106 + 75 mu m-212 + 154 mu m; stirring speed, 500-750 rpm; reaction time, 20-60 min. The findings of this research were given as follows: (1) the optimum operational conditions were found to be reaction temperature 120 degrees C, pressure 30 bar, solid to liquid ratio 0.05 g/ml, stirring speed 750 rpm, reaction time 60 min, particle size -154 + 106 mu m, (2) 92.94 %of B2O3 was taken into solution under optimum condition (2) the sequestration capacity of CO2 was found to be 188 kg per ton ulexite (3) characterization of products by FTIR, SEM, XRD and ICP-OES confirmed that trimethyl borate and CaCO3 were synthesized. The utilization of CO2 in this process could sequester a considerably amount of CO2, therefore it can be contribute to decrease CO2 emission that causes greenhouse effect.
Keywords: Ulexite; CO(2)Capture; Trimethyl Borate; CaCO3; Taguchi